2015
DOI: 10.1542/hpeds.2015-0024
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Hospital Readmission Among Infants With Neonatal Abstinence Syndrome

Abstract: Objective Neonatal abstinence syndrome (NAS) is a postnatal drug withdrawal syndrome that may last for months. Our objective was to determine if infants with NAS are at increased risk for hospital readmission compared with uncomplicated term and late preterm newborns. Methods In this longitudinal retrospective cohort study, administrative data were used for all births from 2006 to 2009 in the New York State Inpatient Database. We identified infants with NAS, born late preterm or uncomplicated term, as indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 35 publications
2
39
0
Order By: Relevance
“…Seven studies included in the final review examined healthcare utilization following the birth hospitalization. These studies are summarized in Table 2 [26]. This study also found that, compared to the other cohorts, NAS infants had higher hospital readmission rates.…”
Section: Healthcare Utilization Among Nas Infantssupporting
confidence: 53%
See 2 more Smart Citations
“…Seven studies included in the final review examined healthcare utilization following the birth hospitalization. These studies are summarized in Table 2 [26]. This study also found that, compared to the other cohorts, NAS infants had higher hospital readmission rates.…”
Section: Healthcare Utilization Among Nas Infantssupporting
confidence: 53%
“…The epidemiological expansion of NAS throughout resource-limited regions, such as rural areas, increases the complexity of providing comprehensive care for these children [7,12]. These factors can negatively affect NAS infants and utilization of healthcare [18,22,[34][35][36][37] Four of the utilization studies employed multivariate analysis to control for maternal and child factors that could influence result [25][26][27][28]. These studies have reported that NAS represents an independent overall health and/or healthcare utilization risk factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Late preterm infants born at 34 0/7 to 36 6/7 weeks' gestation were compared with term infants born at 37 0/7 to 41 6/7 weeks' gestation. Potential confounders included maternal characteristics (maternal age [ 18,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36], !37 years of age], multigravida, preeclampsia or eclampsia, gestational diabetes, premature rupture of membranes, placental abruption, cesarean section, oxytocin use, neighborhood income) and infant characteristics (twin status, sex, small for gestational age [<10 percentile], neonatal care levels of birth hospitals, and infants' complications during birth hospitalizations including hypoglycemia, jaundice, feeding or gastrointestinal problems, cardiorespiratory problems, neurological problems or asphyxia, sepsis). The maternal neighborhood income was categorized into low (the lowest quintile), medium (the second to fourth quintiles), and high level (the highest quintile) based on maternal postal code using Statistics Canada census data.…”
Section: Comparisonsmentioning
confidence: 99%
“…Infants with NAS have an increased risk for adverse postdischarge outcomes, including hospital readmission, child abuse and neglect 76 77. The process for discharging an infant with NAS should begin before the infant is deemed suitable and involves interaction between parents, physicians, social workers and community services.…”
Section: Discharge Planningmentioning
confidence: 99%